2002
DOI: 10.2188/jea.12.305
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Walking Questionnaire for Population-based Prospective Studies in Japan: Comparison with Pedometer.

Abstract: The single-item questionnaire on walking is reasonably reproducible and valid, and useful in studying the health effects of walking among the Japanese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 19 publications
(30 reference statements)
0
35
1
Order By: Relevance
“…', and could choose one out of three options to answer: ! 30 min, 30 min to 1 h, and 1 1 h. The validity of the questionnaire on walking had already been established [17] . We also asked the subjects whether they were able to independently perform basic activities of daily living (ADL) tasks such as eating.…”
Section: Assessment Of Lifestylementioning
confidence: 99%
“…', and could choose one out of three options to answer: ! 30 min, 30 min to 1 h, and 1 1 h. The validity of the questionnaire on walking had already been established [17] . We also asked the subjects whether they were able to independently perform basic activities of daily living (ADL) tasks such as eating.…”
Section: Assessment Of Lifestylementioning
confidence: 99%
“…Validation of the questionnaire for time spent walking (Tsubono et al, 2002) or the food frequency questionnaire (Ogawa et al, 2003) has already been reported. The physical function status was assessed using the six-item measure of the Medical Outcomes Study (MOS) Short-form General Health Survey (Stewart et al, 1988): able to perform vigorous activity (MOS scores of 5 or 6); capable of moderate but not vigorous activity (MOS scores of 2-4); and capable of only low physical activity (MOS scores of 0 or 1).…”
Section: Exposure Datamentioning
confidence: 99%
“…The validity and reproducibility of the question on walking time have been reported elsewhere. 20 We also presented the results of analyses of BMI or patterns of increase in BMI category with further adjustment for green vegetables, total fruit and total energy intake (as a continuous variable), and green tea intake (less than 1 cup day À1 , 1-2, 3-4 and 5 or more cups day…”
Section: Increase In Body Mass Index Category and Mortality T Shimazumentioning
confidence: 99%